On the Throughput Region of Wireless Random Access Protocols with Multi-Packet Reception using Multi-Objective Optimization - Robles, Ramiro (2019)
This article belongs to the Special Issue Selected Papers from the Seventh International Conference on Innovative Computing Technology (INTECH 2017).